2014
DOI: 10.1556/oh.2014.29822
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia

Abstract: Thrombocytopenia alatt a vérlemezkék számbeli csökkenését értjük. Ez a vérzékenység leggyakoribb oka. Klinikailag petechiák, purpurák megjelenése, nyálkahártyavérzés jellemzi. Előfordulhat azonban akár életet fenyegető, emésztő-rendszert vagy központi idegrendszert érintő vérzés is. A haemostaseologiai laboratóriumi vizsgálatok közül a megnyúlt vérzési idő utal thrombocytaeredetű vérzékenységre. Kialakulásában vagy a csontvelői csökkent megakaryopoesis, vagy a fokozott thrombocytapusztulás, illetve a kettő kom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…Under pathophysiological conditions, any factor which could inhibit PLT regeneration, increase their activation or accelerate their death once overwhelming the capacity of self-regulation will cause changes in both PLT count and morphology and thus results in a change in PLT indices. [ 13 ] Researches have shown that activation of the coagulation system, severe infection, trauma, systemic inflammatory reaction syndrome and thrombotic diseases could all result in changes in PLT indices. Reduction in PLT has been proved to be one of the independent risk factors for ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…Under pathophysiological conditions, any factor which could inhibit PLT regeneration, increase their activation or accelerate their death once overwhelming the capacity of self-regulation will cause changes in both PLT count and morphology and thus results in a change in PLT indices. [ 13 ] Researches have shown that activation of the coagulation system, severe infection, trauma, systemic inflammatory reaction syndrome and thrombotic diseases could all result in changes in PLT indices. Reduction in PLT has been proved to be one of the independent risk factors for ICU patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 In critical patients, platelet count and morphology of platelets also change, causing alterations in platelet indices. 22,23 Increased PDW levels have been observed in several conditions. 11,12,24 In a retrospective study, low platelet count, high MPV value, and high PDW value were shown to be associated with more severe disease and a higher risk of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals are asymptomatic if their platelet count is 50 × 10 9 /L or higher (Gauer and Braun, 2012). Patients with a platelet count below 50 × 10 9 /L are more prone to spontaneous bleeding (i.e., mucosal, gastrointestinal, genitourinary, and intracranial bleeding), which is considered as a hematologic emergency (Stasi, 2012; Gado and Domjan, 2014). There are several causes of thrombocytopenia, including infection, malignancy, autoimmune disease, liver disease, disseminated intravascular coagulation, drugs, pregnancy, and coagulopathy (Smock and Perkins, 2014).…”
Section: Introductionmentioning
confidence: 99%